Mysterium mortis w ujęciu Anastazego Synaity - Piasecki, Dariusz (Vox Patrum, 2020)
The article presents the thought of Anastasius Sinaita regarding death from a Christian perspective. The author tries to depict in detail the process of the dying of man. He is concerned not only about the moment of death itself, but also the accompanying circumstances. Hence, the author studies surrounding events which include speeches performed by both the person who is passing away and people surrounding him. The funeral oration is based upon the Biblical text, but also includes various themes from both human and animal life. The homily has a didactic and consolable character.